Asymmetric Organocatalytic Synthesis of Spiro-cyclopropaneoxindoles - Noole, Artur; Malkov, Andrei V.; Kanger, Tõnis (Synthesis, 2013)
Straightforward cascade reactions for the synthesis of spiro-cyclopropaneoxindoles are described. The target compounds are obtained in high yields and in good enantio- and diastereoselectivities via hydrogen bonding or iminium catalysis.
Keywords: spiro compounds; organocatalysis; oxindoles; 3-chlorooxindoles; asymmetric synthesis